Addition of ramucirumab or merestinib to standard first-line chemotherapy for locally advanced or metastatic biliary tract cancer: a randomised, double-blind, multicentre, phase 2 study. Issue 10 (October 2021) - Valle, Juan W; Vogel, Arndt; Denlinger, Crystal S; He, Aiwu Ruth; Bai, Li-Yuan; Orlova, Rashida; Van Cutsem, Eric; Adeva, Jorge; Chen, Li-Tzong; Obermannova, Radka; Ettrich, Thomas J; Chen, Jen-Shi; et al.
Summary: Background: Biliary tract cancers are aggressive, rare, gastrointestinal malignancies with a poor prognosis; approximately half of patients with these cancers survive for less than 1 year after diagnosis with advanced disease. We aimed to evaluate the efficacy and safety of ramucirumab or merestinib in addition to first-line cisplatin–gemcitabine in patients with locally advanced or metastatic biliary tract cancer. Methods: We did a randomised, double-blind, phase 2 study at 81 hospitals across 18 countries. We enrolled patients with histologically or cytologically confirmed, non-resectable, recurrent, or metastatic biliary tract adenocarcinoma, who were treatment-naive, aged 18 years or older, with an Eastern Cooperative Oncology Group performance status of 0 or 1, estimated life expectancy of 3 months or more, and measurable disease per Response Evaluation Criteria in Solid Tumors version 1.1. Eligible participants were randomly assigned (2:1:2:1) to receive either intravenous ramucirumab 8 mg/kg or placebo (on days 1 and 8 in 21-day cycles) or oral merestinib 80 mg or placebo (once daily) until disease progression, unacceptable toxicity, death, or patient or investigator request for discontinuation. All participants received intravenous cisplatin 25 mg/m 2 and gemcitabine 1000 mg/m 2 (on days 1 and 8 in 21-day cycles), for a maximum of eight cycles. Randomisation was done by an interactive web response system using a permuted block method (blocks of six) and was stratified by primary tumour site, geographical region, and presence of metastatic disease. Participants, investigators, and the study funder were masked to treatment assignment within the intravenous and oral groups. The primary endpoint was investigator-assessed progression-free survival (in the intention-to-treat population). The safety analysis was done in all patients who received at least one dose of their assigned treatment. This trial is registered with ClinicalTrials.gov, NCT02711553, and long-term follow-up is ongoing. Findings: Between May 25, 2016, and Aug 8, 2017, 450 patients were assessed for eligibility and 309 (69%) were enrolled and randomly assigned to ramucirumab (n=106), merestinib (n=102), or pooled placebo (n=101); 306 received at least one dose of study treatment. The median follow-up time for progression-free survival at data cutoff (Feb 16, 2018) was 10·9 months (IQR 8·1–14·1). Median progression-free survival was 6·5 months (80% CI 5·7–7·1) in the ramucirumab group, 7·0 months (6·2–7·1) in the merestinib group, and 6·6 months (5·6–6·8) in the pooled placebo group (ramucirumab vs placebo hazard ratio 1·12 [80% CI 0·90–1·40], two-sided stratified p=0·48; merestinib vs placebo 0·92 [0·73–1·15], two-sided stratified p=0·64). The most common grade 3 or worse adverse events were neutropenia (51 [49%] of 104 patients in the ramucirumab group; 48 [47%] of 102 in the merestinib group; and 33 [33%] of 100 in the pooled placebo group), thrombocytopenia (36 [35%]; 19 [19%]; and 17 [17%]), and anaemia (28 [27%]; 16 [16%]; and 19 [19%]). Serious adverse events occurred in 53 (51%) patients in the ramucirumab group, 56 (55%) in the merestinib group, and 48 (48%) in the pooled placebo group. Treatment-related deaths (deemed related by the investigator) occurred in one (1%) of 104 patients in the ramucirumab group (cardiac arrest) and two (2%) of 102 patients in the merestinib group (pulmonary embolism [n=1] and sepsis [n=1]). Interpretation: Adding ramucirumab or merestinib to first-line cisplatin–gemcitabine was well tolerated, with no new safety signals, but neither improved progression-free survival in patients with molecularly unselected, locally advanced or metastatic biliary tract cancer. The role of these targeted inhibitors remains investigational, highlighting the need for further understanding of biliary tract malignancies and the contribution of molecular selection. Funding: Eli Lilly and Company.